Architectural spatial distribution and network connectivity characteristics of ancient military towns in Southwest China: a case study of Qingyan Ancient Town in Guiyang - Yaxing Zhao; Huiwen Xiang; Zongsheng Huang (Heritage Science)
Abstract Due multiple influences, such as Tusi, Tunpu, and minority culture, Tunpu military towns in Southwest China have unique historical and cultural heritage. At present, the ancient Tunpu military towns are not widely known internationally. In order to understand the layout characteristics of Tunpu military buildings in southwest China since the Ming Dynasty, the spatial distribution and military attributes of Qingyan Ancient Town, a typical military town of Tunpu culture, are studied by using Thiessen polygons, fractal theories, and complex network methods. The findings indicate that architectural spaces in the six districts have high spatial self-similarity and low spatial complexity and are distributed in clusters primarily impacted by natural factors and supplemented by humanistic factors. The architectural space networks of the six districts have high stability, low vulnerability, poor balance, and high connectivity. They reflect its interior architectural layout, which is based on close cooperation between villagers and military, taking into account trade and cultural life. Differences in the functionality of buildings lead to differences in the connectivity of the spatial network of buildings; the hierarchical, graded, and differentiated characteristics of architectural spatial network connectivity are influenced by both nature and society. Non-military functions all serve or are subordinate to military functions. The spatial network connectivity of traditional settlement architecture reflects the interaction between nature and society. By studying a Tunpu military ancient town in the southwest, we can better understand the historical military activities, cultural connotations, social changes, and historical background of traditional settlements. The historical planning of the defence of traditional settlements both contributes to its cultural heritage and as an important reference and inspiration for modern planning and management.